If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x^{4}+ -81 = 0 Reorder the terms: -81 + x^{4}= 0 Solving -81 + x^{4}= 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + x^{4}= 0 + 81 Combine like terms: -81 + 81 = 0 0 + x^{4}= 0 + 81 x^{4}= 0 + 81 Combine like terms: 0 + 81 = 81 x^{4}= 81 Simplifying x^{4}= 81 Reorder the terms: -81 + x^{4}= 81 + -81 Combine like terms: 81 + -81 = 0 -81 + x^{4}= 0 Factor a difference between two squares. (9 + x^{2})(-9 + x^{2}) = 0 Factor a difference between two squares. (9 + x^{2})((3 + x)(-3 + x)) = 0## Subproblem 1

Set the factor '(9 + x^{2})' equal to zero and attempt to solve: Simplifying 9 + x^{2}= 0 Solving 9 + x^{2}= 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x^{2}= 0 + -9 Combine like terms: 9 + -9 = 0 0 + x^{2}= 0 + -9 x^{2}= 0 + -9 Combine like terms: 0 + -9 = -9 x^{2}= -9 Simplifying x^{2}= -9 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.## Subproblem 2

Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3## Subproblem 3

Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3## Solution

x = {-3, 3}

| 0.1x-0.05*(2x^2)=1.6x | | 4x^2+6=2x^2 | | 25y^2-20y+3=0 | | 7x^6-6x^7=0.75 | | f(-3)=2x^2-3x+5 | | 3x^3=x | | (26x^6+8x^5-3x^3+33x-12)= | | 26x^6+8x^5-3x^3+33x-12= | | 10x^2=64 | | x^2+-3x=28 | | x^2+12=15 | | x^2+12x=15 | | y=4x^3-28x+24 | | 5x^2=n | | 49x^2+42x+9=25 | | =14x^3*9x | | 2x^2-5x=-5 | | x^2-11x+30=0 | | x^2+6=12 | | 2x^2-19x-12=0 | | 3x^2+4x^2=100 | | 3x^2+4x^2= | | 2x^3-19x-12=0 | | x^3+6x^2-4x=24 | | 0=0.5x^3+3x^2-8 | | 10x^2+41x=0 | | 16w^16+4w^10+2w^4=0 | | x^2+4x+4=4x+4 | | 16x^3-2= | | g^2+4g-32=0 | | 5d^2-22d+8=0 | | 2x^3-7x^2-8x+28= | | 3x^3-9x^2-10x=x^3-2x^2-2x-28 | | 42=x+x^2 | | x^2+17x-3=7x-12 | | x^3-25x=0 | | 4x^2+15x+9=0 | | y=-3.1x^2+20x | | x^2+4x-45=0 | | x^2-x+6=0 | | 12c^2+43+35=0 | | 12c^2+43c+35=0 | | (p+5)x^2+p=19+2p | | x^2-8x+7=0 | | x^2-x+9=0 | | 1-25X^2=0 | | 2x^2-41=0 | | 2x^2-41=5 | | 36x^2+6x-6=0 | | 3x^2-10x+3=0 | | 6x^2-47x=0 | | 2x^2+7x+3=0 | | .66x^2-32=0 | | .66x^2-36=0 | | 16x^2-25=0 | | x^2+6=6x^2-16 | | 3x^2-8=0 | | 3x^2-12=0 | | 9c=c^2 | | X*x=x^2 | | 6x^2+x-c=(cx-1)(3x+2) | | 3x^2-13x+14=0 | | 5x^2-5x-3= | | x^4-3x^2+1=0 | | 6x^2+17x-45=0 |